2022
DOI: 10.3389/fonc.2022.839816
|View full text |Cite
|
Sign up to set email alerts
|

Low Vitamin D Status Predicts Poor Clinical Outcome in Advanced Melanoma Treated With Immune Checkpoint or BRAF/MEK Inhibitors: A Prospective Non-Interventional Side-by-Side Analysis

Abstract: In melanoma and other malignancies, low vitamin D status is associated with increased risk and poor prognosis. However, there are limited data of the impact of 25(OH)D serum concentration (s.c.) on clinical outcome in advanced melanoma. We tested the hypothesis that vitamin D status is predictive of efficacy and safety in patients treated for metastasized melanoma with B-rapidly accelerated fibrosarcoma (BRAF), mitogen-activated protein kinase kinase (MEK), cytotoxic T lymphocyte-associated protein-4 (CTLA-4),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Late responders also reported a trend toward higher values of PUFA energy intake share, vitamin D and anthocyanin consumption, as well as lower reported intake of saturated fatty acid use compared to early responders, which was all previously associated with potentially beneficial effects on the cancer treatment [51,[55][56][57][58][59][60]. A higher use of alcohol was reported in late responders; while chronic alcoholism was linked with the development of various cancers, a potential of alcohol to activate dendritic and natural killer cells and potentially increase PD-L1 protein expression in tumor tissue was also reported [61,62].…”
Section: Discussionmentioning
confidence: 88%
“…Late responders also reported a trend toward higher values of PUFA energy intake share, vitamin D and anthocyanin consumption, as well as lower reported intake of saturated fatty acid use compared to early responders, which was all previously associated with potentially beneficial effects on the cancer treatment [51,[55][56][57][58][59][60]. A higher use of alcohol was reported in late responders; while chronic alcoholism was linked with the development of various cancers, a potential of alcohol to activate dendritic and natural killer cells and potentially increase PD-L1 protein expression in tumor tissue was also reported [61,62].…”
Section: Discussionmentioning
confidence: 88%
“…22 Another study also implicated that even an increase in 25(OH)D of only 1 ng/mL was associated with an up to 3.9% reduced risk for tumor progression. 23 This difference was more pronounced in the irAE subgroup. IrAEs occur as a consequence of immune system overactivation, so irAEs are thought to occur in the face of better treatment responses.…”
Section: Discussionmentioning
confidence: 91%
“…A recent study also indicated that patients with higher plasma 25(OH)D levels had a better treatment response, though there was only a limited number of ICI responders in that study 22. Another study also implicated that even an increase in 25(OH)D of only 1 ng/mL was associated with an up to 3.9% reduced risk for tumor progression 23. This difference was more pronounced in the irAE subgroup.…”
Section: Discussionmentioning
confidence: 92%
“…CYP27B1 was identified in human melanoma tumor tissue [61]. CYP27B1 expressions have been reported to be inversely correlated with the development of melanoma, and low or undetectable levels have been linked to poor prognosis [62,63]. CYP24A1, the most prominent catabolic enzyme, has been detected in tissues expressing VDR and plays a vital role in the local regulation of vitamin D activity [36].…”
Section: Dermal Expression Of Vitamin D-related Cyp Enzymesmentioning
confidence: 99%